All-solid-state lithium ion secondary battery

By using a variety of carbon materials with different particle sizes in the lithium-free anode of all-solid-state lithium-ion batteries, the problem of insufficient contact area between the negative electrode and the solid electrolyte is solved, and the performance and life of the battery are improved.

CN119923730APending Publication Date: 2025-05-02LG ENERGY SOLUTION LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380067155.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-11-04
Filing Date
2023-11-03
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The porosity of lithium-free negative electrodes in existing all-solid-state lithium-ion batteries is relatively large, resulting in insufficient contact area with solid electrolytes, affecting battery performance.

Method used

Two or more carbon materials with different particle sizes are used as components of the negative electrode active material layer to increase the contact area with the solid electrolyte.

Benefits of technology

By reducing the porosity of the lithium-free negative electrode and increasing the contact area with the solid electrolyte, the initial charging/discharge efficiency and life performance of the all-solid state battery are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119923730A_ABST
    Figure CN119923730A_ABST
Patent Text Reader

Abstract

Disclosed is an all-solid-state lithium ion secondary battery in which a lithium-free negative electrode of the all-solid-state battery may include two or more carbon materials having different particle sizes to increase a contact area with a solid electrolyte. The all-solid-state lithium ion secondary battery comprises a positive electrode, a solid electrolyte layer, a negative electrode current collector and a negative electrode active material layer arranged between the solid electrolyte layer and the negative electrode current collector, and the negative electrode active material layer comprises a first carbon material and a second carbon material, a second carbon material; and Ag; wherein the first carbon material and the second carbon material have different average particle sizes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims the benefit of and priority to Korean Patent Application No. 10-2022-0146309, filed on November 4, 2022, and Korean Patent Application No. 10-2023-0150694, filed on November 3, 2023, the disclosures of which are incorporated herein by reference in their entirety.

[0002] The present invention relates to an all-solid-state lithium-ion secondary battery including a lithium-free negative electrode, and more specifically, to an all-solid-state lithium-ion secondary battery, wherein the lithium-free negative electrode of the all-solid-state battery includes two or more carbon materials with different particle sizes to increase the contact area with a solid electrolyte. Background Art

[0003] Various batteries are being studied to overcome the limitations of currently widely commercialized lithium-ion batteries in terms of capacity, safety, power output, large-scale and miniaturization. For example, academia and industry are continuously studying the following batteries: metal-air batteries with very large theoretical capacity compared to lithium-ion batteries, all-solid-state batteries without explosion risk compared to lithium-ion batteries, supercapacitors in terms of power output, sodium-sulfur batteries (NaS batteries) or redox flow batteries (RFBs) in terms of large-scale, and thin-film batteries in terms of miniaturization.

[0004] Among them, the all-solid-state battery is a battery in which the electrolyte used in the lithium secondary battery is replaced by a solid by a liquid. As a result, by not using flammable solvents, fire or explosion caused by the decomposition reaction of conventional electrolytes will not occur at all, so safety can be greatly improved. In addition, the advantage of the all-solid-state battery is that, since lithium metal or lithium alloy can be used as the negative electrode active material, the energy density relative to the mass and volume of the battery can be significantly improved. In addition, the capacity density (capacity per unit weight) of lithium is about 10 times the capacity density of graphite commonly used as a negative electrode active material. Therefore, the use of lithium as a negative electrode active material makes it possible to increase the power output of the all-solid-state battery while thinning the battery.

[0005] As a conventional all-solid-state battery, a battery having a metal layer formed of a metal alloyed with lithium as a negative electrode active material layer and an interface layer composed of amorphous carbon on the negative electrode active material layer is known. In this type of all-solid-state battery, metallic lithium is precipitated between the amorphous carbon interface layer and the negative electrode active material layer during charging, and the precipitated metallic lithium is ionized and moves to the positive electrode during discharge. However, if the all-solid-state battery as described above is repeatedly charged and discharged, the metallic lithium precipitated between the amorphous carbon interface layer and the negative electrode active material layer may be ionized and dissolved to form pores, thereby causing the problem that it cannot be used as a battery.

[0006] To compensate for this problem, the industry has developed an all-solid-state battery having an anode composed of carbon and silver (Ag) and not including a lithium metal layer (i.e., a lithium-free anode). However, in this case, due to the large pores between the carbon materials, the contact area between the anode and the solid electrolyte is small even with warm isostatic pressing (WIP), making it difficult to maximize the performance of the battery.

[0007] In other words, since all-solid-state batteries use only solid materials, good performance can only be achieved by reducing resistance when good contact is achieved between the electrode and the electrolyte. Therefore, isostatic pressing is performed after battery manufacturing to reduce pores and increase the contact area between the electrode and the electrolyte. However, the known lithium-free negative electrode for all-solid-state batteries has large pores between the carbon materials, and even if isostatic pressing is used, the contact area with the solid electrolyte is insufficient. Therefore, a method is needed to reduce the porosity of the lithium-free negative electrode before isostatic pressing and further reduce the porosity after isostatic pressing to increase the contact area with the solid electrolyte layer. Summary of the invention

[0008] [Technical issues]

[0009] Therefore, an object of the present invention is to provide an all-solid-state lithium-ion secondary battery, wherein the lithium-free negative electrode of the all-solid-state battery comprises two or more carbon materials with different particle sizes to increase the contact area with the solid electrolyte.

[0010] [Technical solution]

[0011] In order to achieve the above-mentioned objectives, the present invention provides an all-solid-state lithium-ion secondary battery, which includes a positive electrode, a solid electrolyte layer, a negative electrode current collector, and a negative electrode active material layer arranged between the solid electrolyte layer and the negative electrode current collector, wherein the negative electrode active material layer comprises: a first carbon material; a second carbon material; and Ag, wherein the first carbon material and the second carbon material have different average particle sizes.

[0012] [Effects of the invention]

[0013] According to the all-solid-state lithium-ion secondary battery of the present invention, the lithium-free negative electrode of the all-solid-state battery has the advantage of including two or more carbon materials with different particle sizes to increase the contact area with the solid electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 It is a schematic cross-sectional view showing the structure of an all-solid-state lithium-ion secondary battery according to one embodiment of the present invention.

[0015] Figure 2 It is a schematic cross-sectional view showing the structure of an all-solid-state lithium-ion secondary battery according to one embodiment of the present invention.

[0016] Figure 3 Schematic cross-sectional view of the distribution of active materials in a negative electrode for an all-solid-state battery manufactured according to one embodiment of the present invention.

[0017] Figure 4 It is a cross-sectional schematic diagram of the distribution of active materials in the negative electrode of a conventional all-solid-state battery.

[0018] Figure 5 : is a graph showing the measurement results of the porosity of each of the negative electrodes of one example of the present invention and a comparative example before and after isostatic pressing.

[0019] Figure 6 It is a scanning electron microscope (SEM) image of the surface of each negative electrode of one Example of the present invention and a comparative example.

[0020] Figure 7 3D laser confocal microscope images of the surfaces of the negative electrodes of one example of the present invention and a comparative example.

[0021] Figure 8 It is a graph showing the performance of batteries of one example of the present invention and a comparative example. DETAILED DESCRIPTION

[0022] Hereinafter, the present invention is described in detail.

[0023] The all-solid-state lithium-ion secondary battery of the present invention comprises a positive electrode, a solid electrolyte layer, a negative electrode current collector, and a negative electrode active material layer arranged between the solid electrolyte layer and the negative electrode current collector, wherein the negative electrode active material layer comprises a first carbon material, a second carbon material and Ag, wherein the first carbon material and the second carbon material have different average particle sizes.

[0024] All-solid-state batteries have the advantages of excellent energy density and safety. Typical examples of such all-solid-state batteries are all-solid-state batteries including a metal layer formed of a metal alloyed with lithium as a negative electrode active material layer and an interface layer composed of amorphous carbon on the negative electrode active material layer; and all-solid-state batteries that overcome the above-mentioned disadvantages and have a negative electrode (i.e., a lithium-free negative electrode) composed of carbon and silver (Ag) without a lithium metal layer. However, in the latter case, due to the large pores between the carbon materials, even if warm isostatic pressing (WIP) is adopted, the contact area between the negative electrode and the solid electrolyte is very small, and it is not easy to maximize the performance of the battery. Therefore, the applicant of the present invention has invented an all-solid-state lithium-ion secondary battery, which can reduce the porosity of the lithium-free negative electrode before isostatic pressing, and further reduce the porosity after isostatic pressing to increase the contact area with the solid electrolyte layer.

[0025] Figure 1: is a schematic cross-sectional view of the structure of an all-solid-state lithium-ion secondary battery according to an embodiment of the present invention. An all-solid-state lithium-ion secondary battery (100) according to an embodiment of the present invention is a so-called lithium-ion secondary battery that performs charging and discharging by transferring lithium ions between a positive electrode (10) and a negative electrode (20). Specifically, the all-solid-state lithium-ion secondary battery (100) includes a positive electrode (10), a negative electrode (20), and a solid electrolyte layer (30) disposed between the positive electrode (10) and the negative electrode (20), such as Figure 1 shown.

[0026] Hereinafter, each of these components is described, and in particular, the negative electrode (20) which is a key feature of the present invention is described in more detail.

[0027] (1) positive electrode

[0028] like Figure 1 As shown, the positive electrode (10) includes a positive electrode active material layer (14) and a positive electrode current collector (12) arranged in sequence along the direction of the negative electrode (20). The positive electrode current collector (12) can be in the form of a plate or foil. The positive electrode current collector (12) can be a metal selected from, for example, indium, copper, magnesium, stainless steel, titanium, iron, cobalt, nickel, zinc, aluminum, germanium and lithium, or an alloy of two or more metals.

[0029] The positive electrode active material layer (14) can reversibly absorb and release lithium ions. In addition, the positive electrode active material layer (14) can include a positive electrode active material and also include a solid electrolyte. The positive electrode active material can be a compound capable of inserting / removing lithium. Examples of compounds capable of inserting or removing lithium include: Li a A 1-b B' b D'2 (where 0.90≤a≤1.8 and 0≤b≤0.5); Li a E 1-b B' b O 2-c D' c (where 0.90≤a≤1.8, 0≤b≤0.5 and 0≤c≤0.05); LiE 2-b B' b O 4-c D' c (where 0≤b≤0.5 and 0≤c≤0.05); Li a Ni 1-b-c Co b B' c D' α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05 and 0<α≤2); Li a Ni 1-b-c Cob B' c O 2-α F' α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05 and 0<α<2); Li a Ni 1-b-c Mn b B' c D' α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05 and 0<α≤2); Li a Ni 1-b- c Mn b B' c O 2-α F' α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05 and 0<α<2); Li a Ni b E c G d O2 (where 0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5 and 0.001≤d≤0.1); Li a Ni b Co c Mn d G e O2 (where 0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, 0≤d≤0.5 and 0.001≤e≤0.1); Li a NeG b O2 (where 0.90≤a≤1.8 and 0.001≤b≤0.1); Li a CoG b O2 (where 0.90≤a≤1.8 and 0.001≤b≤0.1); Li a MnG b O2 (where 0.90≤a≤1.8 and 0.001≤b≤0.1); Li a Mn b O4 (where 0.90≤a≤1.8 and 0.001≤b≤0.1); QO2; QS2; LiQS2; V2O5; LiV2O5; LiI'O2; LiNiVO4; Li (3-f) J2(PO4)3(where 0≤f≤2);Li (3-f) Fe2(PO4)3 (where 0≤f≤2); and LiFePO4.

[0030] In the above formula, A is Ni, Co, Mn, or a combination thereof; B' is Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, a rare earth element, or a combination thereof; D' is O, F, S, P, or a combination thereof; E is Co, Mn, or a combination thereof; F' is F, S, P, or a combination thereof; G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V, or a combination thereof; Q is Ti, Mo, Mn, or a combination thereof; I is Cr, V, Fe, Sc, Y, or a combination thereof; J is V, Cr, Mn, Co, Ni, Cu, or a combination thereof.

[0031] Specific examples of the positive electrode active material include lithium salts such as lithium cobaltate (LCO), lithium nickelate, lithium nickel cobaltate, lithium nickel cobalt aluminate (NCA), lithium nickel cobalt manganate (NCM), lithium manganate, lithium iron phosphate, and lithium sulfide. The positive electrode active material layer (14) may include only one selected from these compounds as the positive electrode active material, or may include two or more selected therefrom.

[0032] The positive electrode active material may include a lithium salt of a transition metal oxide having a layered rock salt structure among the above lithium salts. Here, the layered rock salt structure means that oxygen atom layers and metal atom layers are alternately and regularly arranged in the direction of the cubic rock salt structure, resulting in a structure in which each atomic layer forms a two-dimensional plane. In addition, the cubic rock salt structure means a sodium chloride-type structure which is one of the crystal structures. For example, the cubic rock salt structure means a structure in which face-centered cubic lattices having cations and anions are arranged by shifting 1 / 2 of the corners of the unit cell from each other.

[0033] The lithium salt of a transition metal oxide having such a layered rock salt-type structure may be, for example, a ternary lithium transition metal oxide, such as LiNi x Co y Al z O2 (NCA) or LiNi x Co y Mn z O2 (NCM) (where 0 < x < 1, 0 < y < 1, 0 < z < 1 and x + y + z = 1). The positive electrode active material layer (14) may include a lithium salt of a ternary lithium transition metal oxide having such a layered rock salt-type structure as the positive electrode active material to improve the energy density and thermal stability of the all-solid-state lithium ion secondary battery (100).

[0034] The shape of the positive electrode active material may be, for example, a particulate shape, such as a spherical shape or an oval shape. In addition, the particle size of the positive electrode active material is not particularly limited and may be within the range of the positive electrode active material applicable to a conventional all-solid-state lithium ion secondary battery. In addition, the content of the positive electrode active material in the positive electrode active material layer (14) is not particularly limited and may be within the range of the positive electrode applicable to a conventional all-solid-state lithium ion secondary battery.

[0035] In addition, a compound having a coating on the surface can be used, and a mixture of the above-mentioned compound and a compound having a coating can be used. The coating may include a coating element compound of an oxide or hydroxide of a coating element, an oxyhydroxide of a coating element, an oxycarbonate of a coating element, or a hydroxycarbonate of a coating element. The compound constituting the coating may be amorphous or crystalline. Examples of coating elements contained in the coating may include Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr, or a mixture thereof, and a specific example of the coating may include Li2O-ZrO2. Any coating method (e.g., spraying, impregnation, etc.) may be used to form the coating, as long as the compound can be coated with these elements in a manner that does not adversely affect the properties of the positive electrode active material, which is easily understandable to those skilled in the art, and therefore, a detailed description thereof is not provided herein.

[0036] The solid electrolyte that may be further included in the positive electrode active material layer (14) may be the same as the solid electrolyte included in the solid electrolyte layer (30) described later, or may be different therefrom. In addition, the positive electrode active material layer (14) may be a combination of not only the above-mentioned positive electrode active material and solid electrolyte, but also additives such as conductive materials, adhesives, fillers, dispersants or ion conductive aids. Such conductive materials may include, for example, graphite, carbon black, acetylene black, Ketjen black, carbon fiber or metal powder. In addition, the adhesive may be mixed with the active material and the conductive material to bind the components together and contribute to the growth of the particles, and may be, for example, styrene butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride or polyethylene. In addition, the filler, dispersant or ion conductive aid may be those commonly used in electrodes of all-solid-state lithium ion secondary batteries. In addition, the positive electrode active material layer (14) may include the above-mentioned positive electrode active material, conductive material and adhesive in particle form.

[0037] (2) negative electrode

[0038] Next, the negative electrode (20) includes a negative electrode active material layer (24) and a negative electrode current collector (22) arranged in sequence along the direction of the positive electrode (10). The negative electrode current collector (22) may be in the form of a plate or foil. The negative electrode current collector (22) may contain a material that does not react with lithium, i.e., does not form any alloy or compound with lithium. Examples of materials constituting the negative electrode current collector (22) include copper, stainless steel, titanium, iron, cobalt, and nickel. In addition, the negative electrode current collector (22) may be composed of one of these metals, or may be composed of an alloy or coating material of two or more metals.

[0039] The negative electrode active material layer (24) may contain one or more negative electrode active materials that can form an alloy or compound with lithium. In the initial state or after full discharge, the negative electrode current collector (22), the negative electrode active material layer (24), or the region between the negative electrode active material layer (24) and the solid electrolyte layer (30) may not contain lithium. Figure 2 1 is a schematic cross-sectional view of the structure of an all-solid-state lithium-ion secondary battery according to an embodiment of the present invention. As described below, when an all-solid-state lithium-ion secondary battery (100) according to an embodiment is overcharged, the negative electrode active material contained in the negative electrode active material layer (24) and the lithium ions migrated from the positive electrode (10) can form an alloy or a compound, so that, for example, a metal layer (26) containing lithium as a main component can be formed (precipitated) on the negative electrode (20), such as Figure 2 As shown. The metal layer (26) can be formed by precipitation between the negative electrode current collector (22) and the negative electrode active material layer (24), inside the negative electrode active material layer (24), or at both locations. When the metal layer (26) is located between the negative electrode current collector layer (22) and the negative electrode active material layer (24), the metal layer (26) can be formed closer to the negative electrode current collector layer (22) than the negative electrode active material layer (24).

[0040] According to one embodiment of the present invention, the negative electrode active material layer (24) contains silver (Ag) as an essential negative electrode active material. Therefore, the metal layer (26) formed during overcharge may include a Li (Ag) alloy including a γ1 phase, a βLi phase, or a combination thereof in which Ag is solid-dissolved in lithium. Therefore, during discharge, only Li may be dissolved in the Li (Ag) alloy constituting the metal layer (26), while the solid-dissolved Ag may be retained to suppress the generation of pores. In this case, the content of Ag in the precipitated Li-Ag solid solution may be 60 wt % or less. Within this range, the decrease in the average discharge potential due to the influence of Ag may be effectively suppressed. On the other hand, if the content of Ag in the precipitated Li-Ag solid solution is too small, the amount of Ag remaining during discharge will be very small, and it may be difficult to fully suppress the generation of pores. For this reason, the content of Ag in the precipitated Li-Ag solid solution may be 20 wt % or more, for example, 40 wt % or more.

[0041] In one embodiment of the present invention, Ag is not necessarily uniformly present in the negative electrode active material layer (24), and may be unevenly distributed on one side of the negative electrode current collector (22) of the negative electrode active material layer (24). In this case, the Li(Ag) alloy may be formed into a metal layer (26) by reacting lithium ions with the layer of the negative electrode active material layer (24) where the Ag is unevenly distributed near the negative electrode current collector (22).

[0042] If the content of Ag contained in the negative electrode active material layer (24) is too low, the amount of Ag remaining during discharge also decreases, so it may be difficult to suppress the generation of pores. For this reason, in the initial state where charging or discharging is not performed, the negative electrode active material layer (24) may contain 10% by weight or more, preferably 20% by weight or more, of Ag based on 100% by weight of all negative electrode active materials contained in the negative electrode active material layer (24). On the other hand, in the relationship between the reaction potentials of Ag and Li, an increase in Ag can reduce the average discharge potential, thereby reducing the energy density of the battery. Therefore, in terms of high energy density, the upper limit of the Ag content may preferably be 50% by weight or less based on 100% by weight of all negative electrode active materials contained in the negative electrode active material layer (24).

[0043] In addition, if the Ag content per unit area in the negative electrode active material layer (24) is too low when viewed from the stacking direction of the negative electrode (20), the amount of Ag remaining during discharge is also reduced, so it may be difficult to suppress the generation of pores. Therefore, the Ag content per unit area in the negative electrode active material layer (24) may be 0.05 mg / cm 2 Above, preferably 0.10 mg / cm 2 On the other hand, if the Ag content per unit area is too high, the average discharge potential may decrease and the energy density of the battery may decrease. Therefore, the upper limit of the Ag content per unit area may be 5 mg / cm 2 Below, preferably 2mg / cm 2 the following.

[0044] In addition, Ag contained in the negative electrode active material layer (24) may be in a particle phase or a film phase in its initial state of not being charged and discharged. If Ag is present in a particle phase, the average particle size (d50, diameter length or average diameter) of Ag may be, but is not limited to, 20 nm to 1 μm.

[0045] Meanwhile, the negative electrode active material layer (24) may contain a carbon material as a negative electrode active material other than Ag, and may further include one or more selected from the group consisting of Au, Pt, Pd, Si, Al, Bi, Sn, In and Zn as necessary.

[0046] Carbon material in the negative electrode active material layer

[0047] The negative electrode active material layer (24) includes two or more carbon materials with different average particle sizes. More specifically, the negative electrode active material layer (24) includes a first carbon material and a second carbon material, wherein the first carbon material and the second carbon material have different average particle sizes (D50).

[0048] This is to reduce the pores in the negative electrode active material layer (24) to increase the contact area between the negative electrode (20) and the solid electrolyte layer (30). In other words, if the negative electrode active material layer (24) contains two or more carbon materials with different average particle sizes, the carbon material with a relatively small particle size is located between the carbon materials with a relatively large particle size, thereby reducing the porosity of the negative electrode active material layer (24) before isostatic pressing (i.e., increasing the density of the negative electrode active material layer). In addition, after isostatic pressing is achieved in this state, the porosity of the negative electrode active material layer (24) can be further reduced to maximize the increase in the contact area with the solid electrolyte layer. Therefore, compared with conventional cases, the initial charge / discharge efficiency and life performance of the all-solid-state battery can be significantly improved.

[0049] The average particle size ratio of the first carbon material to the second carbon material may be 1:1.2 to 4, preferably 1:1.5 to 3, and more preferably 1:1.8 to 2.7. If the average particle size ratio of the first carbon material to the average particle size of the second carbon material falls outside 1:1.2 to 4, the purpose of the present invention may not be achieved, or the effect may be maximized and there may be no further benefit.

[0050] For example, the average particle size of the first carbon material may be greater than 5 nm and less than 50 nm, and the average particle size of the second carbon material may be greater than 50 nm and less than 90 nm. In addition, it may be more preferred that the average particle size of the first carbon material is 25 nm to 45 nm, and the average particle size of the second carbon material is 60 nm to 85 nm. In particular, if the negative electrode active material layer (24) contains a carbon material with an average particle size of greater than 100 nm, the purpose of the present invention cannot be achieved, so it is preferred that both the first carbon material and the second carbon material have an average particle size of tens of nanometers. In other words, the negative electrode active material layer (24) does not contain a carbon material with an average particle size of greater than 100 nm.

[0051] In addition, the difference in average particle size between the first carbon material and the second carbon material may be 10 nm to 50 nm, preferably 20 nm to 45 nm, more preferably 30 nm to 40 nm. If the difference in average particle size between the first carbon material and the second carbon material is less than 10 nm, it may be difficult to maximize the benefit of the difference in average particle size, and if it exceeds 50 nm, there may be no further benefit.

[0052] In addition, the content ratio of the first carbon material to the second carbon material may be 2:8 to 8:2 by weight, preferably 1 to 4:1. If the content ratio of the first carbon material to the second carbon material falls outside the range of 2:8 to 8:2 by weight, the reduction in the porosity of the negative electrode active material layer (24) may not be significant or beneficial. In addition, based on 100% by weight of all negative electrode active materials contained in the negative electrode active material layer (24), the content of the remaining negative electrode active material other than Ag may be 50% by weight or more, preferably 70% by weight or more.

[0053] On the other hand, two or more carbon materials with different average particle sizes may be included in the negative electrode active material layer (24), so that the carbon materials are mixed with each other and the carbon material with a relatively small particle size is located between the carbon materials with a relatively large particle size, such as Figure 3 In this case, the entire negative electrode active material layer (24) has uniform and fine pores, resulting in a high overall density.

[0054] However, in the negative electrode active material layer (24), only the carbon material with a relatively small particle size (i.e., the first carbon material) is located alone on the interface side with the solid electrolyte layer (30), so that the interface between the negative electrode active material layer (24) and the solid electrolyte layer (30) can be further flattened. Therefore, in this case, the negative electrode active material layer (24) can be divided into a first negative electrode active material layer in which only the first carbon material is located alone and a second negative electrode active material layer in which the first carbon material and the second carbon material are mixed. Of course, the first negative electrode active material layer and the second negative electrode active material layer can each contain Ag. In other words, the negative electrode active material layer (24) can include: a first negative electrode active material layer containing the first carbon material and Ag; and a second negative electrode active material layer containing the first carbon material, the second carbon material and Ag. In the first negative electrode active material layer and the second negative electrode active material layer, the first negative electrode active material layer is in contact with the solid electrolyte layer (30).

[0055] Here, the thickness ratio of the first negative electrode active material layer to the second negative electrode active material layer may be 1:5 to 1:10, preferably 1:7 to 1:10. Here, the thickness of the first negative electrode active material layer refers to the thickness of the thinnest portion from the interface of the negative electrode active material layer (24) in contact with the solid electrolyte layer (30) to the position in contact with the second negative electrode active material layer. In addition, the thickness of the second negative electrode active material layer refers to the thickness of the thickest portion from the position in contact with the negative electrode current collector (22) to the position in contact with the first negative electrode active material layer.

[0056] The first carbon material and the second carbon material may be of the same or different species. In addition, it is preferred that the first carbon material and the second carbon material are each amorphous carbon without a crystalline structure. More specifically, the first carbon material and the second carbon material may each independently be amorphous carbon black, amorphous acetylene black, amorphous furnace black, amorphous Ketjen black, amorphous activated carbon, amorphous graphene or a combination thereof. Therefore, the first carbon material and the second carbon material may include, for example, an amorphous carbon black having an average particle size of 5 nm or more and less than 30 nm and an amorphous carbon black having an average particle size of 30 nm or more and less than 90 nm. In addition, the first carbon material and the second carbon material may include, for example, an amorphous furnace black having an average particle size of 5 nm or more and less than 30 nm and an amorphous graphene having an average particle size of 30 nm or more and less than 90 nm.

[0057] In addition, the first carbon material and the second carbon material may each independently include at least one of point-like particles having an aspect ratio of 1 to 2 and linear particles having an aspect ratio greater than 2. However, preferably, the first carbon material and the second carbon material are both point-like particles having an aspect ratio of 1 to 2, and even more preferably, they are point-like particles whose aspect ratio converges to 1, so that the carbon material having a relatively small particle size (e.g., the first carbon material) can be smoothly and evenly distributed between the carbon material having a relatively large particle size (e.g., the second carbon material).

[0058] Although the negative electrode active material layer (24) is described above as including the first carbon material and the second carbon material having different average particle sizes, it is obvious that the negative electrode active material layer (24) may further include several other carbon materials having average particle sizes different from those of the first carbon material and the second carbon material.

[0059] Meanwhile, the two or more carbon materials having different average particle sizes contained in the negative electrode active material layer (24) may each contain oxygen. More specifically, each carbon material particle constituting the carbon material may contain 2 to 10 atomic % of oxygen. When oxygen is included in the range of 2 to 10 atomic %, the surface roughness of the negative electrode active material layer and the driving characteristics of the battery may be further improved.

[0060] In one embodiment of the present invention, oxygen may be present in the form of being incorporated into a functional group bound to the carbon material particles. In addition, the functional group may include one or more selected from the group consisting of a carboxyl group, a hydroxyl group, an ether, an ester, an aldehyde group, a carbonyl group, and an amide group.

[0061] Carbon material particles containing 2 to 10 atomic % of oxygen can be prepared, for example, by oxidizing the carbon material. In one embodiment of the present invention, oxygen functional groups can be introduced to the surface of the carbon material by treating the carbon material with an acid and stirring and reacting at a temperature of 25°C to 60°C. The type of acid is not particularly limited, and can be any acid capable of introducing oxygen functional groups to the surface of the carbon material. The acid can be, for example, sulfuric acid, nitric acid, or a mixture thereof, and an oxidizing agent such as potassium permanganate can also be used.

[0062] The oxygen content in the carbon material particles can be measured using photoelectron spectroscopy (XPS or ESCA). For example, a K-Alpha (Thermo Fisher Scientific) device can be used to measure. In one embodiment of the present invention, oxygen may be present on the surface of the carbon material particles. The surface does not necessarily refer to the outer surface of the carbon material particles, but includes, for example, the inner surface of the pores (if there are pores).

[0063] If the carbon material contains oxygen as described above, the negative electrode active material layer (24) may contain 2 to 10 atomic % of oxygen, 65 to 85 atomic % of carbon, and 0.5 to 5 atomic % of Ag, preferably 2.5 to 5 atomic % of oxygen, 74 to 85 atomic % of carbon, and 0.5 to 3 atomic % of Ag. In addition, the negative electrode active material layer (24) may further contain 5 to 25 atomic %, preferably 10 to 20 atomic % of fluorine (F). In addition, the negative electrode active material layer (24) may further contain 0.01 to 1 atomic %, preferably 0.01 to 0.5 atomic % of sulfur (S). In one embodiment of the present invention, the negative electrode active material layer (24) may contain 2 to 10 atomic % oxygen, 65 to 85 atomic % carbon, 0.5 to 5 atomic % Ag and 5 to 25 atomic % fluorine, preferably 2.5 to 5 atomic % oxygen, 74 to 85 atomic % carbon, 0.5 to 3 atomic % Ag and 10 to 20 atomic % fluorine, and may further contain sulfur. The above atomic composition ratio can be measured using photoelectron spectroscopy (XPS or ESCA). For example, the above ratio can be measured using a Nexsa4 (Thermo Fisher Scientific) device.

[0064] In order to stabilize the negative electrode active material layer (24) on the negative electrode current collector (22), the negative electrode active material layer (24) may further include a binder. The binder may be, for example, a resin such as styrene butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride or polyethylene. In addition, the negative electrode active material layer (24) may be appropriately formulated with additives used in conventional all-solid-state batteries, such as fillers, dispersants or ion conductive aids. Specific examples of additives are the same as those described in the above-mentioned positive electrode.

[0065] The total thickness of the negative electrode active material layer (24) is not particularly limited, and may be, for example, 1 to 100 μm. If the thickness of the negative electrode active material layer (24) is less than 1 μm, the performance of the all-solid-state battery may be insufficient. In addition, if the thickness of the negative electrode active material layer (24) exceeds 100 μm, the resistance of the negative electrode active material layer (24) may increase, and thus the performance of the all-solid-state battery may be insufficient. For reference, by using the above-mentioned binder, the thickness of the negative electrode active material layer (24) can be easily ensured to an appropriate level.

[0066] The negative electrode current collector (22) may further include a film containing a material capable of forming an alloy or compound with lithium, and the film may be disposed between the negative electrode current collector (22) and the negative electrode active material layer (24). The negative electrode current collector (22) may not react with lithium metal, but it may be difficult to precipitate a smooth lithium metal layer on the top. In addition, the film may also be used as a wetting layer to allow lithium metal to be smoothly precipitated on the top of the negative electrode current collector (22).

[0067] The material used in the film that can form an alloy with lithium metal may include silicon, magnesium, aluminum, lead, silver, tin or a combination thereof. The material used in the film that can form a compound with lithium metal may include carbon, titanium sulfide, iron sulfide or a combination thereof. The content of the material used in the film can be a small amount without affecting the electrochemical properties of the electrode and / or the redox potential of the electrode. The film can be applied flatly on the negative electrode collector (22) to prevent cracks from occurring during the charging cycle of the all-solid-state battery. The application of the film can be performed by physical deposition (e.g., evaporation or sputtering), chemical deposition or plating. The thickness of the film can be, for example, 1 to 500 nm. The thickness of the film can be, for example, 2 to 400 nm. The thickness of the film can be, for example, 3 to 300 nm. The thickness of the film can be, for example, 4 to 200 nm. The thickness of the film can be, for example, 5 to 100 nm.

[0068] (3) Solid electrolyte layer

[0069] The solid electrolyte layer (30) is provided between the positive electrode (10) and the negative electrode (20) (for example, between the positive electrode active material layer (14) and the negative electrode active material layer (24)), and includes a solid electrolyte capable of moving ions. The solid electrolyte may include one or more selected from a sulfide-based solid electrolyte, a polymer-based solid electrolyte, and an oxide-based solid electrolyte, and may preferably include only a sulfide-based solid electrolyte.

[0070] Sulfide solid electrolytes may include Li2S-P2S5, Li2S-P2S5-LiX (wherein X is a halogen atom), Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (where m and n are positive numbers, Z is any one of Ge, Zn and Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li p MO q (wherein p and q are positive numbers, and M is any one of P, Si, Ge, B, Al, Ga, and In) or a combination thereof. The sulfide-based solid electrolyte may include a solid electrolyte represented by the following Chemical Formula 1.

[0071] [Chemical formula 1]

[0072] Li x M' y PS z A w ,

[0073] wherein x, y, z and w are independently at least 0 and not more than 6, M' is at least one selected from As, Ge, Ga, Sb, Si, Sn, Al, In, Ti, V, Nb and Ta, and A is at least one selected from F, Cl, Br and I.

[0074] As a solid electrolyte, a sulfide solid electrolyte material comprising sulfur (S), phosphorus (P) and lithium (Li) can be used. For example, a composition comprising Li2S-P2S5 can be used. When a sulfide solid electrolyte material comprising Li2S-P2S5 is used, the mixed molar ratio of Li2S and P2S5 can be selected in the range of, for example, 50:50 to 90:10. In addition, the solid electrolyte can be amorphous, crystalline or a mixture of amorphous and crystalline. In addition, the solid electrolyte layer (30) can further include a binder. The binder can be, for example, a resin, such as styrene butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, polyethylene or polyacrylic acid. The binder can be the same or different from the binder respectively contained in the positive active material layer (14) and the negative active material layer (24).

[0075] Initial charge capacity ratio

[0076] In addition, the all-solid-state lithium-ion secondary battery (100) of one embodiment of the present invention may be configured such that the initial charge capacity of the positive electrode active material layer (14) is in excess of the initial charge capacity of the negative electrode active material layer (24). As described below, the all-solid-state lithium-ion secondary battery (100) of one embodiment may be charged to exceed the initial charge capacity of the negative electrode active material layer (24). At the beginning of charging, lithium may be adsorbed in the negative electrode active material layer (24), that is, the negative electrode active material may form an alloy or compound with lithium ions migrated from the positive electrode (10). When charging is performed to exceed the initial charge capacity of the negative electrode active material layer (24), lithium may precipitate from the back side of the negative electrode active material layer (24), that is, between the negative electrode current collector (22) and the negative electrode active material layer (24), and a metal layer (26) may be formed from the lithium, such as Figure 2 As shown. The metal layer (26) may be mainly composed of lithium in which Ag is solid-dissolved (i.e., Ag-Li solid solution). It may be composed of a negative electrode active material (e.g., a material that forms an alloy or compound with lithium). During discharge, the lithium in the negative electrode active material layer (24) and the metal layer (26) may be ionized and migrate to the positive electrode (10) side while leaving behind the Ag in the lithium. Therefore, lithium can be used as a negative electrode active material in an all-solid-state lithium-ion secondary battery (100). In addition, since the negative electrode active material layer (24) coats the metal layer (26), it can act as a protective layer for the metal layer (26) and inhibit the precipitation and growth of dendrite metal lithium.

[0077] The all-solid-state lithium-ion secondary battery (100) of one embodiment of the present invention preferably has a ratio (b / a) of the initial charge capacity of the positive electrode active material layer (14) to the initial charge capacity of the negative electrode active material layer (24) that satisfies the following mathematical formula.

[0078] [Mathematical formula 1]

[0079] 0.01

[0080] In Formula 1, a is the initial charge capacity (mAh) of the positive electrode active material layer (14), and b is the initial charge capacity (mAh) of the negative electrode active material layer (24).

[0081] ​If the initial charge capacity ratio is below 0.01, the negative electrode active material layer (24) may not be sufficient to act as a protective layer, and the characteristics of the all-solid-state lithium ion secondary battery (100) may deteriorate. For example, if the thickness of the negative electrode active material layer (24) is very thin, the capacity ratio may be below 0.01. In this case, the negative electrode active material layer (24) may collapse due to repeated charging and discharging, and dendrite metal lithium may precipitate and grow. Therefore, the characteristics of the all-solid-state lithium ion secondary battery (100) may deteriorate. On the other hand, if the initial charge capacity ratio is above 0.5, the battery capacity may decrease due to the reduction in the amount of lithium precipitation in the negative electrode.

[0082] Method for preparing all-solid-state lithium-ion secondary battery

[0083] Next, a method for manufacturing an all-solid-state lithium-ion secondary battery (100) is provided. The all-solid-state lithium-ion secondary battery (100) of one embodiment of the present invention can be manufactured by separately preparing a positive electrode (10), a negative electrode (20) and a solid electrolyte layer (30), and then stacking them.

[0084] First, in the process of manufacturing the positive electrode, the materials constituting the positive electrode active material layer (14) (positive electrode active material, binder, etc.) are added to a non-polar solvent to prepare a slurry (or paste), and then the prepared slurry is applied to the positive electrode collector (12) and dried to obtain a laminate. The laminate can then be pressurized (e.g., hydrostatically pressurized) to manufacture the positive electrode (10). In this case, the pressurization process can be omitted.

[0085] Next, the method for manufacturing the negative electrode includes adding the material constituting the negative electrode active material layer (24) (including two or more carbon materials with different average particle sizes and Ag negative electrode active materials and a binder, etc.) to a polar solvent or a non-polar solvent to prepare a slurry (or paste), and then applying the prepared slurry to the negative electrode collector (22) and drying to obtain a laminate. The laminate can then be pressurized (e.g., hydrostatic pressure) to manufacture the negative electrode (20). In this case, the pressurization process can be omitted. In addition, the method for applying the slurry to the negative electrode collector (22) is not particularly limited, and may include, for example, screen printing, metal mask printing, electrostatic coating, dip coating, spray coating, roller coating, blade coating, or gravure coating.

[0086] Next, a solid electrolyte including, for example, a sulfide-based solid electrolyte material can be used to prepare a solid electrolyte layer (30). First, a starting material (e.g., Li2S or P2S5) is processed by a melt quenching method or a mechanical grinding method to obtain a sulfide-based solid electrolyte material. For example, when a melt quenching method is used, the starting materials are mixed in a predetermined amount, granulated, reacted at a predetermined reaction temperature in a vacuum, and then quenched to produce a sulfide-based solid electrolyte material. In addition, the reaction temperature of the mixture of Li2S and P2S5 can be 400°C to 1000°C, for example, 800°C to 900°C. In addition, the reaction time can be 0.1 hours to 12 hours, for example, 1 hour to 12 hours. In addition, the quenching temperature of the reactant can be below 10°C, for example, below 0°C, and the quenching rate can generally be 1°C / second to 10000°C / second, for example, 1°C / second to 1000°C / second. In addition, when a mechanical grinding method is used, a sulfide-based solid electrolyte material can be prepared by stirring and reacting the starting materials using a ball mill. In addition, the stirring speed and stirring time of the mechanical milling method are not particularly limited, but the faster the stirring speed, the faster the sulfide solid electrolyte material can be produced, and the longer the stirring time, the higher the conversion rate of the raw material to the sulfide solid electrolyte material.

[0087] Then, the obtained mixed raw material (sulfide solid electrolyte material) is heat-treated at a predetermined temperature and then crushed to produce a granular solid electrolyte. If the solid electrolyte has a glass transition point, it can be transformed from amorphous to crystalline by heat treatment. Subsequently, the solid electrolyte obtained by the above method can be film-formed using a known film-forming method (such as an aerosol positioning method, a cold spray method or a sputtering method) to produce a solid electrolyte layer (30). In addition, the solid electrolyte layer (30) can be prepared by pressurizing the solid electrolyte particles. In addition, the solid electrolyte layer (30) can be prepared by mixing the solid electrolyte with a solvent and a binder, and then coating, drying and pressurizing.

[0088] Finally, a solid electrolyte layer (30) may be disposed between the prepared positive electrode (10) and negative electrode (20), and pressurized, for example, by hydrostatic pressure, to manufacture an all-solid-state lithium-ion secondary battery (100) according to one embodiment of the present invention.

[0089] Charging method of all-solid-state lithium-ion secondary battery

[0090] Next, a charging method of the all-solid-state lithium-ion secondary battery (100) is described. The charging method of the all-solid-state lithium-ion secondary battery (100) of one embodiment of the present invention may be to charge (i.e., overcharge) the all-solid-state lithium-ion secondary battery (100) exceeding the charging capacity of the negative electrode active material layer (24). At the beginning of charging, lithium may be adsorbed within the negative electrode active material layer (24). When charging exceeds the charging capacity of the negative electrode active material layer (24), lithium may precipitate from the back side of the negative electrode active material layer (24), i.e., between the negative electrode current collector (22) and the negative electrode active material layer (24), and lithium may form a metal layer (26) that does not exist during manufacturing, such as Figure 2 As shown. In addition, during discharge, lithium in the negative electrode active material layer (24) and the metal layer (26) can be ionized and migrate to the positive electrode (10) side. Therefore, in the all-solid-state lithium ion secondary battery (100) of the present invention, lithium can be used as a negative electrode active material. In addition, since the negative electrode active material layer (24) is coated with the metal layer (26), it can act as a protective layer for the metal layer (26) while inhibiting the precipitation and growth of dendrite metal lithium. In this way, short circuit and capacity degradation of the all-solid-state lithium ion secondary battery (100) can be suppressed, and in addition, the characteristics of the all-solid-state lithium ion secondary battery (100) can be improved.

[0091] Furthermore, according to one embodiment of the present invention, the metal layer (26) is not preformed, which has the advantage of reducing the manufacturing cost of the all-solid-state lithium-ion secondary battery (100). Figure 2 The metal layer (26) is shown as being formed between the negative electrode current collector (22) and the negative electrode active material layer (24), but may also be formed inside the negative electrode active material layer (24). In addition, the metal layer (26) may be formed between the negative electrode current collector (22) and the negative electrode active material layer (24) and inside the negative electrode active material layer (24) at the same time.

[0092] The all-solid-state lithium ion secondary battery (100) of the present invention can be manufactured as a unit cell having a positive electrode / separator / negative electrode structure, a double core having a positive electrode / separator / negative electrode / separator / positive electrode structure, or a stacked cell having the structure of the unit cell repeated. In addition, the all-solid-state lithium ion secondary battery of the present invention can include a liquid electrolyte as required, thereby being used as a semi-solid-state battery, in which case it can further include a separate polymer separator.

[0093] The shape of the all-solid-state lithium ion secondary battery (100) of the present invention is not particularly limited, and may include a coin type, a button type, a sheet type, a stacked type, a cylindrical type, a flat type or an angular type. It can also be applied to large batteries used in electric vehicles. For example, the all-solid-state lithium ion secondary battery (100) can be used in hybrid vehicles, such as plug-in hybrid electric vehicles (PHEV). They can also be used in applications requiring large amounts of power storage, such as electric bicycles or electric tools.

[0094] In the following, preferred embodiments are given to facilitate the understanding of the present invention, but it is obvious to those skilled in the art that the following embodiments are merely examples of the present invention, and various changes and modifications can be made within the scope of the present invention and technical concept, and these changes and modifications fall within the scope of the attached patent claims.

[0095] [Example 1] Preparation of negative electrode for all-solid-state battery

[0096] First, 3 g of amorphous carbon black with an average particle size of 40 nm, 3 g of amorphous carbon black with an average particle size of 80 nm, 2 g of Ag, 9.33 g of PVdF binder (6% solids) and 7.67 g of NMP solvent were placed in a Thinky mixer container and mixed at 2,000 rpm for 12 times for 3 minutes each. Then 5 g of NMP solvent was added and mixed at 2,000 rpm for 5 times for 3 minutes each to prepare a negative electrode active material slurry, which was then coated on SUS foil and dried to prepare a negative electrode for an all-solid-state battery.

[0097] [Example 2] Preparation of negative electrode for all-solid-state battery

[0098] First, 3 g of amorphous carbon black with an average particle size of 40 nm, 3 g of amorphous Ketjen black with an average particle size of 80 nm, 2 g of Ag, 9.33 g of PVdF binder (6% solids) and 7.67 g of NMP solvent were placed in a Thinky mixer container and mixed at 2,000 rpm for 12 times for 3 minutes each. Then 5 g of NMP solvent was added and mixed at 2,000 rpm for 5 times for 3 minutes each to prepare a negative electrode active material slurry, which was then coated on SUS foil and dried to prepare a negative electrode for an all-solid-state battery.

[0099] [Example 3] Preparation of negative electrode for all-solid-state battery

[0100] First, 4.5 g of amorphous carbon black with an average particle size of 40 nm, 1.5 g of amorphous carbon black with an average particle size of 80 nm, 2 g of Ag, 9.33 g of PVdF binder (6% solids) and 7.67 g of NMP solvent were placed in a Thinky mixer container and mixed at 2,000 rpm for 12 times for 3 minutes each. Then 5 g of NMP solvent was added and mixed at 2,000 rpm for 5 times for 3 minutes each to prepare a negative electrode active material slurry, which was then coated on SUS foil and dried to prepare a negative electrode for an all-solid-state battery.

[0101] [Example 4] Preparation of negative electrode for all-solid-state battery

[0102] First, 3 g of amorphous carbon black with an average particle size of 40 nm and an oxygen content of 2.6 atomic %, 3 g of amorphous carbon black with an average particle size of 80 nm, 2 g of Ag, 9.33 g of PVdF binder (6% solids) and 7.67 g of NMP solvent were placed in a Thinky mixer container and mixed at 2,000 rpm for 12 times for 3 minutes each time. Then, 5 g of NMP solvent was added and mixed at 2,000 rpm for 5 times for 3 minutes each time to prepare a first negative active material slurry, which was then applied to a SUS foil and dried.

[0103] Next, 1 g of amorphous carbon black having an average particle size of 40 nm and an oxygen content of 2.6 atomic %, 0.3 g of Ag, 1.5 g of PVdF binder (6% solids) and 2.5 g of NMP solvent were added to a Thinky mixer container and mixed at 2,000 rpm for 12 times for 3 minutes each. Then, 1.5 g of NMP solvent was added and mixed at 2,000 rpm for 5 times for 3 minutes each to prepare a second negative electrode active material slurry, which was then applied to the surface of the dried first negative electrode active material slurry and dried to prepare a negative electrode for an all-solid-state battery.

[0104] [Comparative Example 1] Preparation of negative electrode for all-solid-state battery

[0105] First, 6 g of amorphous carbon black with an average particle size of 40 nm, 2 g of Ag, 9.33 g of PVdF binder (6% solids) and 7.67 g of NMP solvent were placed in a Thinky mixer container and mixed at 2,000 rpm for 12 times for 3 minutes each. Then 5 g of NMP solvent was added and mixed at 2,000 rpm for 5 times for 3 minutes each to prepare a negative electrode active material slurry, which was then coated on SUS foil and dried to prepare a negative electrode for an all-solid-state battery.

[0106] [Comparative Example 2] Preparation of negative electrode for all-solid-state battery

[0107] First, 6 g of amorphous carbon black with an average particle size of 120 nm, 2 g of Ag, 9.33 g of PVdF binder (6% solids) and 7.67 g of NMP solvent were placed in a Thinky mixer container and mixed at 2,000 rpm for 12 times for 3 minutes each. Then 5 g of NMP solvent was added and mixed at 2,000 rpm for 5 times for 3 minutes each to prepare a negative electrode active material slurry, which was then coated on SUS foil and dried to prepare a negative electrode for an all-solid-state battery.

[0108] [Comparative Example 3] Preparation of negative electrode for all-solid-state battery

[0109] First, 3 g of amorphous carbon black with an average particle size of 120 nm, 3 g of amorphous carbon black with an average particle size of 200 nm, 2 g of Ag, 9.33 g of PVdF binder (6% solids) and 7.67 g of NMP solvent were placed in a Thinky mixer container and mixed at 2,000 rpm for 12 times for 3 minutes each. Then 5 g of NMP solvent was added and mixed at 2,000 rpm for 5 times for 3 minutes each to prepare a negative electrode active material slurry, which was then coated on SUS foil and dried to prepare a negative electrode for an all-solid-state battery.

[0110] [Experimental Example 1] Evaluation of the distribution of negative electrode before and after isostatic pressing

[0111] The negative electrodes for all-solid-state batteries manufactured in Examples 1 to 3 and Comparative Examples 1 and 2 were cut along the stacking direction to observe the distribution of the carbon material in the negative electrode active material layer, and the results were modeled and shown in Figure 3 and 4 (Ag is not shown in order to facilitate identification of the distribution between carbon materials). Figure 3 is a cross-sectional schematic diagram of the distribution of active materials of a negative electrode for an all-solid-state battery manufactured according to one embodiment of the present invention, wherein Figure 3 (a) shows the image before isostatic pressing, Figure 3 (b) is the image after isostatic pressing. Figure 4 It is a cross-sectional schematic diagram of the distribution of active materials in the negative electrode of a conventional all-solid-state battery, where Figure 4 (a) is the image before isostatic pressing. Figure 4 (b) is the image after isostatic pressing.

[0112] First, see Figure 4 , the distribution of the carbon material in the negative electrode active material layer prepared in Comparative Example 1 or 2 shows that when only one type of carbon material is used, even before isostatic pressing ( Figure 4 (a)), the porosity is also larger, and even after isostatic pressing ( Figure 4(b)), the reduction in porosity is also minimal. On the other hand, in the carbon materials of the negative electrode active material layer prepared in Examples 1 to 3, such as Figure 3 As shown in (a), the porosity is significantly reduced before isostatic pressing, and as Figure 3 As shown in (b), after isostatic pressing, not only the overall porosity is further reduced, but also the interface near the solid electrolyte layer becomes very flat compared to Comparative Examples 1 and 2.

[0113] That is, this is due to the use of carbon materials with relatively large particle sizes and carbon materials with relatively small particle sizes as negative electrode active materials, and it can be clearly predicted that the contact area between the negative electrode and the solid electrolyte layer is expanded and the performance of the battery can be improved.

[0114] [Experimental Example 2] Measuring and evaluating the porosity of negative electrodes

[0115] The porosity of each of the negative electrodes for all-solid-state batteries prepared in Example 1 and Comparative Examples 1 to 3 before and after isostatic pressing was measured, and the results are shown in Table 1 below. Figure 5 : is a graph showing the measurement results of the porosity of each of the negative electrodes of one example of the present invention and the comparative example before and after isostatic pressing, which is a graphical representation of Table 1 below.

[0116] [Table 1]

[0117]

[0118] From Table 1 and Figure 5 It can be seen that, like the negative electrode prepared in Example 1 above, the porosity is reduced by isostatic pressing in the negative electrodes prepared in Comparative Examples 1 and 2. However, in Example 1 using a mixture of two carbon materials, the porosity reduction rate by isostatic pressing is about 36%, which is a relatively high porosity reduction rate compared to Comparative Example 1 (porosity reduction rate: 33%) and Comparative Example 2 (porosity reduction rate: 27%) using only one carbon material.

[0119] Most importantly, Example 1 using a mixture of two carbon materials exhibits a higher density than Comparative Examples 1 and 2 even before isostatic pressing, and thus exhibits a lower porosity than Comparative Examples 1 and 2 using only one carbon material even after isostatic pressing when the pores are reduced.

[0120] In addition, compared with Comparative Example 3 using a mixture of amorphous carbon black having an average particle size of 120 nm and amorphous carbon black having an average particle size of 200 nm, Example 1 using a mixture of amorphous carbon black having an average particle size of 40 nm and amorphous carbon black having an average particle size of 80 nm showed lower porosity and higher porosity reduction rate. This shows that even when a mixture of two carbon materials is used, when the average particle size exceeds the level of tens of nanometers, the porosity increases and the contact area with the solid electrolyte decreases.

[0121] [Experimental Example 3] Observe the surface of the negative electrode (1)

[0122] The surface of each of the negative electrodes for all-solid-state batteries prepared in Example 1 and Comparative Example 2 (specifically, the surface of the Ag / C layer) was observed by a scanning electron microscope (SEM) (respectively at 100-fold magnification). The results are shown in Figure 6 middle. Figure 6 is a scanning electron microscope (SEM) image of the surface of each negative electrode of an embodiment of the present invention and a comparative example, wherein Figure 6 (a) is a scanning electron microscope (SEM) image of the surface of the negative electrode of Example 1, Figure 6 (b) is a scanning electron microscope (SEM) image of the surface of the negative electrode of Comparative Example 2.

[0123] As a result of the observation, it was observed that the negative electrode surface of Comparative Example 2 using only one carbon material had a plurality of surface protrusions such as Figure 6 On the other hand, compared with Comparative Example 2, the negative electrode surface of Example 1 using a mixture of two carbon materials showed a significant improvement in surface protrusions, as shown in FIG. Figure 6 As shown in (a).

[0124] [Experimental Example 4] Observe the surface of the negative electrode (2)

[0125] The surface roughness of each of the negative electrodes for all-solid-state batteries manufactured in Example 1 and Comparative Examples 1 and 2 above (specifically, the surface of the Ag / C layer) was measured using a 3D laser confocal microscope apparatus (manufactured by KEYENCE), and the results are shown in Tables 2 and 3 below. Figure 7 middle. Figure 7 3D laser confocal microscope images of the surfaces of the negative electrodes of an embodiment of the present invention and a comparative example, wherein Figure 7 (a) is a 3D laser confocal microscope image of the surface of the negative electrode of Example 1, Figure 7 (b) is a 3D laser confocal microscope image of the surface of the negative electrode of Comparative Example 1. Figure 7 (c) is a 3D laser confocal microscope image of the surface of the negative electrode of Comparative Example 2.

[0126] Specifically, prepare the negative electrode whose roughness is to be measured in a suitable size. At this time, prepare more than three samples of the same electrode to ensure the reliability of the data and check the roughness deviation. Attach these samples to a glass slide using double-sided tape to prevent wrinkling. Then place the glass slide with the prepared sample on the measuring stage, focus, and measure the roughness.

[0127] [Table 2]

[0128] Sa(μm) Sz(μm) Example 1 0.07 0.92 Comparative Example 1 0.13 1.13 Comparative Example 2 0.18 1.52

[0129] *Sa: arithmetic mean roughness of the surface, Sz: maximum height roughness of the surface

[0130] [Example 5, Comparative Examples 4 to 6] Preparation of all-solid-state lithium-ion secondary batteries

[0131] The load used is 5.5 mAh / cm 2 The positive electrode of the positive electrode active material is used as the positive electrode, the respective negative electrodes prepared in Example 1 and Comparative Examples 1 to 3 are used as the negative electrode, and a sulfide solid electrolyte is used as the electrolyte to manufacture the pouch-type single cells of Example 5 and Comparative Examples 4 to 6.

[0132] [Experimental Example 5] Evaluating battery characteristics

[0133] The pouch-type single cells of Example 5 and Comparative Examples 4 to 6 were operated in an operating voltage range of 4.25 V to 3.0 V and an operating temperature of 60° C. under the following charge and discharge conditions to evaluate the cycle characteristics. The results are shown in Figure 8 middle.

[0134] -Charging conditions: 0.33C, 4.25V CC / CV, 0.1C cut-off

[0135] -Discharge conditions: 0.33C, 3.0V, CC

[0136] Figure 8 Graph showing the performance of a battery of one embodiment of the present invention and a comparative example. The cycle characteristics of the pouch-type single cells of embodiment 5 and comparative examples 4 to 6 were evaluated. Figure 8 As shown, the battery of Example 5 using a negative electrode having a mixture of two types of carbon materials exhibits higher cycle characteristics than the batteries of Comparative Examples 4 and 5 using a negative electrode having only one type of carbon material. It can be seen that when a carbon material with a relatively large particle size and a carbon material with a relatively small particle size are applied to the negative electrode together, the contact area between the negative electrode and the solid electrolyte layer increases, and the performance of the battery is improved.

[0137] In addition, the battery of Example 5 having a negative electrode containing amorphous carbon black having an average particle size of 40 nm and amorphous carbon black having an average particle size of 80 nm exhibited higher cycle characteristics than the battery of Comparative Example 6 having a negative electrode containing a mixture of amorphous carbon black having an average particle size of 120 nm and amorphous carbon black having an average particle size of 200 nm. It can be seen from this that even if a carbon material with a relatively large particle size and a carbon material with a relatively small particle size are applied to the negative electrode together, the performance of the battery will be reduced when the average particle size exceeds the level of tens of nanometers.

Claims

1. An all-solid-state lithium-ion secondary battery, comprising a positive electrode, a solid electrolyte layer, a negative electrode current collector, and a negative electrode active material layer disposed between the solid electrolyte layer and the negative electrode current collector, in, The negative electrode active material layer comprises: a first carbon material; a second carbon material; and Ag, The first carbon material and the second carbon material have different average particle sizes.

2. The all-solid-state lithium-ion secondary battery according to claim 1, wherein: The ratio of the average particle size of the first carbon material to the average particle size of the second carbon material is 1:1.2 to 4.

3. The all-solid-state lithium-ion secondary battery according to claim 1, wherein: The average particle size of the first carbon material is greater than or equal to 5 nm and less than 50 nm, and the average particle size of the second carbon material is greater than or equal to 50 nm and less than or equal to 90 nm.

4. The all-solid-state lithium-ion secondary battery according to claim 3, wherein: The average particle size of the first carbon material is 25 nm to 45 nm, and the average particle size of the second carbon material is 60 nm to 85 nm.

5. The all-solid-state lithium-ion secondary battery according to claim 1, wherein: The difference in average particle size between the first carbon material and the second carbon material is 10 to 50 nm.

6. The all-solid-state lithium-ion secondary battery according to claim 1, wherein: The negative electrode active material layer does not include a carbon material having an average particle size of 100 nm or more.

7. The all-solid-state lithium-ion secondary battery according to claim 1, wherein: The first carbon material and the second carbon material each independently include at least one of dot-shaped particles having an aspect ratio of 1 to 2 and linear particles having an aspect ratio of more than 2.

8. The all-solid-state lithium-ion secondary battery according to claim 7, wherein: The first carbon material and the second carbon material are dot-shaped particles having an aspect ratio of 1 to 2.

9. The all-solid-state lithium-ion secondary battery according to claim 2, wherein: The content ratio of the first carbon material to the second carbon material is 2:8 to 8:2 by weight.

10. The all-solid-state lithium-ion secondary battery according to claim 2, wherein: The negative electrode active material layer includes: a first negative electrode active material layer including a first carbon material and Ag; and a second negative electrode active material layer including a first carbon material, a second carbon material and Ag, Among them, the first negative electrode active material layer and the second negative electrode active material layer are in contact with a solid electrolyte layer.

11. The all-solid-state lithium-ion secondary battery according to claim 10, wherein: A thickness ratio of the first negative electrode active material layer to the second negative electrode active material layer is 1:5 to 1:

10.

12. The all-solid-state lithium-ion secondary battery according to claim 1, wherein: The first carbon material and the second carbon material are of the same kind or of different kinds.

13. The all-solid-state lithium-ion secondary battery according to claim 1, wherein: The first carbon material and the second carbon material are each amorphous carbon.

14. The all-solid-state lithium-ion secondary battery according to claim 12, wherein: The first carbon material and the second carbon material are each independently selected from the group consisting of amorphous carbon black, amorphous acetylene black, amorphous furnace black, amorphous Ketjen black, amorphous activated carbon, amorphous graphene, and combinations thereof.

Citation Information

Patent Citations

  • Turning aid pad and turning aid mattress

    KR1020220146309A

  • Antenna module inclding structure for expansing ground and electronic device including same

    KR1020230150694A